2015
DOI: 10.1063/1.4914867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nonequilibrium electron-phonon coupling and thermal conductance at interfaces

Abstract: We study the electron and phonon thermal coupling mechanisms at interfaces between gold films with and without Ti adhesion layers on various substrates via pump-probe time-domain thermoreflectance. The coupling between the electronic and the vibrational states is increased by more than a factor of five with the inclusion of an $3 nm Ti adhesion layer between the Au film and the nonmetal substrate. Furthermore, we show an increase in the rate of relaxation of the electron system with increasing electron and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 63 publications
10
107
0
1
Order By: Relevance
“…To determine the size of the error bars, the FDTR-measured phase-lag vs. heating frequency data was fit to the heat diffusion equation to extract the deviations in G when At a metal-dielectric interface, electrons that carry heat within the metal transfer it to phonons that transmit the energy across the interface in a process known as electron-phonon coupling [41]. Electron-phonon coupling has been modeled as a thermal resistance process that is in series with the phonon energy transmission across the interface [42][43][44]. The values of G reported in Figure 2 represent the composite G due to the electron-phonon coupling conductance (G e-p ) and the phonon transmission conductance (G p ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the size of the error bars, the FDTR-measured phase-lag vs. heating frequency data was fit to the heat diffusion equation to extract the deviations in G when At a metal-dielectric interface, electrons that carry heat within the metal transfer it to phonons that transmit the energy across the interface in a process known as electron-phonon coupling [41]. Electron-phonon coupling has been modeled as a thermal resistance process that is in series with the phonon energy transmission across the interface [42][43][44]. The values of G reported in Figure 2 represent the composite G due to the electron-phonon coupling conductance (G e-p ) and the phonon transmission conductance (G p ).…”
Section: Resultsmentioning
confidence: 99%
“…These pathways are i) metal electron–metal phonon coupling at the metal/nonmetal interface ( h e−mp ), ii) phonon–phonon coupling across the interface ( h p−p ), and iii) metal electron–nonmetal phonon coupling directly across the interface ( h e−nmp ). At a metal/nonmetal interface, electronic contributions to interfacial conductance have been mostly suggested to be nonexistent under equilibrium conditions . The interest in this topic was triggered by the seminal work from Stoner and Maris where they reported measurements of h K between a series of metals and nonmetals to which they compared with various phonon–phonon interface models and found discrepancies between theory and experiments .…”
Section: Effect Of Electron Scattering On Thermal Boundary Conductancementioning
confidence: 99%
“…However, recent theoretical works based on the two‐temperature model have suggested that strong electron–phonon coupling in the metal can lead to an increase in the phonon–phonon thermal conductance, while for weak electron–phonon coupling in the metal, this resistive pathway could become significant . There have also been several experimental works that have argued that under time scales where there is strong nonequilibrium between electrons and phonons in the metal, h e−nmp could potentially increase the rate of energy exchange at the interface . For example, Giri et al studied electron and phonon thermal coupling mechanisms at interfaces between gold films with and without Ti adhesion layers on various substrates via pump–probe technique.…”
Section: Effect Of Electron Scattering On Thermal Boundary Conductancementioning
confidence: 99%
“…The notion of a surface oxidized membrane acting as an NPM—with the disordered oxygen atoms covering the membrane surface acting as the nanoresonators—was proposed by Xiong et al NPMs in the form of branched nanoribbon materials composed of molybdenum disulfide (MoS 2 ) were studied by Liu et al Giri and Hopkins and Yang and co‐workers extended the NPM concept to carbon nanotubes and graphene sheets, respectively. Another intriguing NPM architecture is based on a graphene sheet with branching fullerene nanoresonators . Other than thermal conductivity reduction, the impact of nanopillars on the heat capacity was investigated by Iskander et al using both theory and experiments .…”
Section: Thermal Transport In Nanostructured Membranesmentioning
confidence: 99%